TEST SOME VARIETY OF PEANUT plant (Arachis hypogaea L.) ON THE GRANT OF ORGANIC FERTILIZER ON FISH - Sri Utami; Nursamsi ,; Hengko Posda Ramedi Tondang (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The purpose of this study to determine the test several varieties of peanut (Arachis hypogaea  L.) against organic fertilizer fish, using a plot design Divided (RPT) which consists of two factors, namely, varieties factor (V) as the main plot that consists of 2 levels : V1 = varieties Elephant, V2 = varieties rabbits and Fish fertilizer factor (I) as a subplot which consists of 4 levels: I0 = Without fertilizer application (control), I1 = 10 tonnes / ha = 1 kg / plot, I2 = 30 ton / ha = 3 kg / plot, I3= 50 tonnes / ha = 5 kg / plot, and one each in repeat three times. The parameters observed among others: plant height (cm), number of branches (branch), number of pods per plant samples (pods), number of pods per plot (pod), seed weight per plant sample (g), seed weight per plot (g ), and the weight of 100 seeds (g). The results showed that the factors giving Variety shows Elephant better varieties of varieties Rabbits of all parameters were observed. As for the factors giving the best Organic Fertilizer Fish on giving I2 = 30 tonnes / ha = 3 kg / plot.Keywords: Variety, Fertilizers Fish, Peanut, Growth, Production